The influence of physico - chemical parameters on water scale precipitation on washing machines heaters - Doberšek, Danijela (Acta chimica slovenica, 2007)
The paper presents the results of analysis of physico - chemical parameters influence on the intensity of water scale precipitation on washing machines heaters. Washing machines of the same producer were, to this end, modified to an endless cycle of washing with the same amount of cotton fabric at the same conditions. On the basis of various experiments it was determined that water hardness, the amount of exceeded carbon dioxide, water turbulence around the heater, the amount of cotton fibres in water exceeded from fabrics, and heater specific heat strength have the key role in water scale building up in washing machines heaters.
Keywords: električni grelec; kalcijev karbonat; pralni stroji; vodni kamen